2009
DOI: 10.1021/am900394y
|View full text |Cite
|
Sign up to set email alerts
|

Design of Highly Oleophobic Cellulose Surfaces from Structured Silicon Templates

Abstract: Structured silicon surfaces, possessing hierarchical porous characteristics consisting of micrometer-sized cavities superimposed upon a network of nanometer-sized pillars or wires, have been fabricated by a plasma-etching process. These surfaces have superoleophobic properties, after being coated with fluorinated organic trichlorosilanes, on intrinsically oleophilic surfaces. By comparison with flat silicon surfaces, which are oleophilic, it has been demonstrated that a combination of low surface energy and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 60 publications
0
58
0
Order By: Relevance
“…In the Wenzel regime (Fig. 2b), the difference of the measured  CA from the 'true' contact angle of a flat surface ( F ) was described as follows: 40 where R is the ratio between the actual surface area of the rough surface and the apparent area. In this regime, surface roughness can promote either wettability ( CA < 90°) or non-wettability ( CA > 90°), depending on the chemical property of the surface.…”
Section: Static Contact Anglementioning
confidence: 99%
See 4 more Smart Citations
“…In the Wenzel regime (Fig. 2b), the difference of the measured  CA from the 'true' contact angle of a flat surface ( F ) was described as follows: 40 where R is the ratio between the actual surface area of the rough surface and the apparent area. In this regime, surface roughness can promote either wettability ( CA < 90°) or non-wettability ( CA > 90°), depending on the chemical property of the surface.…”
Section: Static Contact Anglementioning
confidence: 99%
“…26 27 demonstrated that superamphiphobic surface could be obtained perfluorosilanerendered TiO 2 /single-walled carbon nanotube composite coatings. Interestingly, the wetting ability of such coatings could be tuned from superoleophobic to superoleophilic via ultraviolet 40 irradiation. Moreover, by controlling the dose of UV illumination, superphobicity and superphilicity can exist on the same surface for probing liquids with different surface tensions.…”
Section: Functionalization With Nanoparticles (Np)mentioning
confidence: 99%
See 3 more Smart Citations